Pengaruh Penggunaan Media Pembelajaran Interaktif Terhadap Prestasi Belajar Siswa Kelas IV Sekolah Dasar - Barus, Nofita Jayanti; Mustika, Dea (Cetta: Jurnal Ilmu Pendidikan, 2024)
Most of the fourthgrade students at SDS Muhammadiyah Duri experienced difficulty in improving their test scores and assignments. One factor that is thought to influence this is the lack of use of learning media by teachers in the learning process. Therefore, this research aims to determine the effect of using interactive learning media on student learning achievement. This research uses a quantitative approach with experimental methods and a one-shot case study design, where the effects of using learning media are tested after one treatment. The research population included all 98 class IV students, while the sample was determined randomly using random sampling techniques, resulting in 24 students from class IV A as research subjects. Data were analyzed using the paired sample t-test statistical test to see differences in student achievement before and after treatment. The research results show that the use of interactive learning media has a significant influence on increasing student learning achievement, with a significance value (Sig. 2-tailed) < 0.000, which is smaller than the significance limit of 0.05. Thus, it can be concluded that interactive learning media effectively helps improve student achievement, showing a strong relationship between its use and learning outcomes. This research provides empirical evidence about the importance of innovation in teaching methods to improve the quality of education.